Edukasi Kesehatan Dalam Meningkatkan Kesadaran Masyarakat Tentang Risiko Diabetes Melitus Di Kelurahan Basirih - Sri Purwanti Ariani; Ernawati .; Rapika . (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
The health education activity on diabetes mellitus risk in Basirih Village aimed to improve community knowledge and awareness through counseling, leaflets, and interactive discussions. The results showed an increase in community understanding after the intervention, indicated by participants’ ability to identify risk factors, signs and symptoms, and prevention efforts for diabetes mellitus, along with a positive shift toward healthier lifestyle behaviors. The outputs of this activity include a scientific article that has been submitted to a national journal and an educational poster currently in the process of intellectual property rights (IPR) registration. The implementation was supported by village partners and local health workers through the provision of facilities and coordination assistance, although several challenges were encountered, such as limited participant attendance, varying levels of understanding, and the time required for administrative processes of the outputs. Future activities will focus on continuous mentoring, strengthening the role of community health cadres, and developing educational media to ensure sustainable and optimal behavioral changes in the community.